Determinan Pertumbuhan Total Aset Bank Umum Syariah Di Indonesia - Nisel Gustika; Husni Shabri; Elfina Yenti; Nofrivul Nofrivul (Al-bank: Journal of Islamic Banking and Finance, 2024)
The study aims to analyze the effect of Non-Performing Finance, Financing Depocit Ratio, Operating Cost of Operating Income and Inflation on the growth of Total Assets of Islamic Commercial Banks in Indonesia. This type of research is quantitative research. The data used in this study is data that has been combined for all Islamic Commercial Banks from 2018-2022. The data collection technique uses documentation sourced from Islamic banking statistical reports on the OJK website and the BI website. Data analysis techniques using multiple linear regression. The results showed that the Financing Depocit Ratio and Operating Cost of Operating Income partially influenced the Growth of Total Assets of Islamic Commercial Banks in Indonesia. While Non-Performing Finance and Inflation partially have no effect on the Growth of Total Assets of Islamic Commercial Banks in Indonesia. Simultaneously there is an influence of NPF, FDR, BOPO and Inflation on the Growth of Total Assets of BUS in Indonesia. The contribution of independent variables to the growth of Total Assets is 84%.